The model of social employment and the protection of the rights of participants of a social integration center - Kuczyński, Tomasz (Studia Iuridica Toruniensia, 2024)
The article deals with the issue of the model of social employment currently adopted by the legislator under the Act of 13 June 2003 on social employment. Threads of legal measures to protect the interests of candidates for participants of classes at the Social Integration Centre as well as the participants themselves were discussed. Attention was also devoted to the Individual Program of Social Employment, the essence of which was presented against the background of the institution of an administrative contract.